ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 78/PUU-XXI/2023 TENTANG PENGHAPUSAN LARANGAN PENYEBARAN BERITA HOAKS PERSPEKTIF SIYASAH DUSTURIYAH - Rio Surya Darmawan; Mustofa; Lutfi Fahrul Rizal (CV Rewang Rencang, 2024)
Freedom of expression and opinion is one of the rights guaranteed by the Constitution, but this freedom is increasingly threatened by articles in the ITE Law and the Criminal Code that regulate the prohibition of spreading hoaxes. These articles are considered to be open to multiple interpretations and lack clear boundaries. The Constitutional Court Decision Number 78/PUU-XXI/2023 has become a breath of fresh air for the democratic climate in Indonesia by annulling these articles. This research aims to analyze the Constitutional Court Decision 78/PUU-XXI/2023 from the perspective of siyasah dusturiyah. This research method uses a normative juridical approach, with literature sources from books, journals, as well as laws or rulings. In the Constitutional Court Decision 78/PUU-XXI/2023, which was tested by Fathia and Haris, it was based on the legal uncertainty regarding the spread of hoax news that they had previously experienced. From that court ruling, it has fostered a better democratic climate and is in line with the paradigm of siyasah dusturiyah. Providing substantial certainty and capable of meeting the needs and desires of the community.